ANALISIS YURIDIS PERAN BANK TANAH BAGI REFORMA AGRARIA DALAM UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA: Juridical Analysis of The Role of Land Banks For Agrarian Reform in Law Number 11 of 2020 Concerning Job Creation - Novery, Aprilia Wulan; Pandamdari, Endang (Faculty of Law, Universitas Trisakti, 2024)
Land banks are specialized institutions with the responsibility of planning, acquiring, buying, maintaining,utilizing, and distributing land. In light of the Agrarian Reform Act of 2020 (Law No. 11 of 2020), thisarticle brings up the question of land banks as a means to further the goal of the law. The papers publishedhere meet the norms of professional legal study. This study intends to analyze land banks from a legal andphilosophical standpoint. This study's results clarify how Government Regulation 64 of 2021 andPresidential Regulation 113 of 2021 define land banks as providers for agricultural reform, as mandatedby Job Creation Law No. 11 of 2020. The Land Bank is obligated to actively participate in supplying landfor agrarian reform and allocate at least 30% of the land area under its control to this purpose. Inconclusion, the Job Creation Law requires the Land Bank to be governed in a way that allows it to fulfillits role as a land-providing agency, gather land for future development, and manage that property in away that upholds the ideals of equity, legal certainty, and legal benefits. Bank.